2018
DOI: 10.1016/j.socscimed.2018.08.033
|View full text |Cite
|
Sign up to set email alerts
|

How might neighborhood built environment influence child maltreatment? Caregiver perceptions

Abstract: Our findings suggest that aspects of the neighborhood built environment, such as the presence of abandoned houses or the lack of recreational centers, can be stressors themselves and may also critically alter families' thresholds for navigating other everyday pressures. Conversely, aspects of the neighborhood built environment, such as housing density, may work to mitigate the risk of maltreatment, either by promoting social support or by increasing the likelihood that maltreatment is reported to authorities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…This contrasts with key tenets of community‐based research paradigms, which hold that community insight regarding health change and disease etiology is crucial for any type of health intervention (Wallerstein & Duran, 2006). For example, efforts that build children's playgrounds to increase leisure time physical activity could lead to new but abandoned playgrounds if families find them inaccessible because of concerns for child safety due to neighborhood violence not obvious to well‐intentioned outsiders (Colabianchi et al, 2009; Haas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with key tenets of community‐based research paradigms, which hold that community insight regarding health change and disease etiology is crucial for any type of health intervention (Wallerstein & Duran, 2006). For example, efforts that build children's playgrounds to increase leisure time physical activity could lead to new but abandoned playgrounds if families find them inaccessible because of concerns for child safety due to neighborhood violence not obvious to well‐intentioned outsiders (Colabianchi et al, 2009; Haas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Though individuals' daily lives extend beyond the geographic bounds of the physical neighborhood (see Cagney et al, 2020), local neighborhood social networks remain important contexts for health and well‐being. For instance, caregivers have noted the presence of accessible parks and other neighborhood green space as important settings for facilitating relational health (e.g., social interaction and parenting social support) (Haas et al, 2018). Studies have additionally found that older adults who perceive greater neighborhood social cohesion are more likely to engage in physical activity which, in turn, bolsters mental health (Kim et al, 2020; Kowitt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…1 Further, our understanding of the epidemiology of child maltreatment has increased in the years since the development of our current child welfare system. We now know that maltreatment results from a complex array of stressors, such as poverty and material hardship (e.g., Cancian et al 2013;Maguire-Jack and Font 2017;Pelton 2015;Slack et al 2017;Warren and Font 2015;Yang 2015;Yang and Maguire-Jack 2016), neighborhood disadvantage (Coulton et al 2018;Drake and Pandey 1996;Freisthler 2004;Maguire-Jack and Font 2017;McLeigh et al 2018), lack of social support (e.g., Freisthler et al 2014;Thompson 1995Thompson , 2015Turner and Avison 1985) and community cohesion (e.g., Barnhart and Maguire-Jack 2016;Emery et al 2015;Garbarino and Kostelny 1992; Kim and Maguire-Jack 2015; Maguire-Jack and Showalter 2016; Maguire-Jack and Wang 2016; Molnar et al 2016;Weissbourd and Grimm 1981;Zolotor and Runyan 2006), the built environment (Haas et al 2018;McDonell and Skosireva 2009) and changing family dynamics (e.g., Melton et al 2002). Indeed, mounting research evidence from as early as the 1980s has suggested that comprehensive child maltreatment prevention efforts need to address communitylevel structures and processes (e.g., Barry 1994;Belsky 1980;Garbarino and Kostelny 1992;Garbarino and Sherman 1980;Melton 1992; National Commission on Children 1991; Schorr 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic created a new reality. On the one hand, more time in the home environment increases the likelihood of domestic violence against women and children; on the other hand, social distancing and work restrictions make it more difficult to identify individuals and families, and provide care and assistance to victims of violence, because of the constant presence of the perpetrators at home, among other reasons (Coulton et al , 2007; Haas et al , 2018; Warren and Font, 2015). According to NCC data, between 2019 and 2020, there was a 19% decrease in the number of minors identified by HMOs as victims of domestic violence and sexual assault, and reported to welfare authorities or the police (NCC, 2021).…”
mentioning
confidence: 99%